DEVELOPMENT OF FIELD WORK PRACTICE MANAGEMENT IN INFORMATICS INTEGRATED SERVICE SYSTEM - Astuti, Indah Fitri; Hendi, Hendi; Cahyadi, Dedy; Kridalaksana, Awang Harsa (Jurnal Pilar Nusa Mandiri, 2024)
Field work practice is crucial for aligning college education with workplace skills, but manual management poses challenges such as time-consuming processes and limited information access, particularly within the Informatics Program at Mulawarman University. This research explores integrating field work practice with mobile technology through Rapid Application Development, resulting in a comprehensive field work practice management mobile app. Data collected from direct observation and student questionnaires inform the app's development. The app covers various field work practice aspects, facilitating efficient student engagement, and Black Box testing confirms its functionality without errors. This research significantly contributes to field work practice management, offering stakeholders an efficient, transparent, and well-integrated solution for field work practice implementation in academic settings, ultimately aiming to enhance convenience and accelerate the field work practice process for all involved parties.